Household Market and Nonmarket Activities (HUS) A Pilot Study - Anders Klevmarken (The Research Institute of Industrial Economics (IUI), 1982)
Economic analysis of household micro behavior, data collection for a longitudinal data base and development of statistical methods for collection and analysis of micro data are the three general purposes of the HUS-project. A pilot study was carried out in 1981/82. It was designed to compare various data collection methods, test questionnaires, give an idea of the likely response rate in a main study, help in developing coding and editing procedures and give the project staff training in the entire survey operation. The pilot study included a sample survey of 300 households which were interviewed in person and by telephone. This report gives an account of the design and the results of the pilot study.
Keywords: C42; C81; D10; 330; Household behavior; Data collection; Survey